1980
DOI: 10.1111/j.1365-2885.1980.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the isoxazolyl penicillins, cloxacillin and flucloxacillin, in serum and synovia of horses

Abstract: Cloxacillin and flucloxacillin were administered to horses by single intravenous dose (25, 33 or 44 mg/kg). Levels of these compounds were assayed biologically from serum and synovia of the carpal and tibio‐tarsal joints at intervals up to 360 min. Serum levels of cloxacillin at 30 min were all in excess of 48 μg/ml and were equal to, or higher than, those given by the equivalent doses of flucloxacillin. Highly significant differences (P<0.001) between doses and between sampling times (30, 60, 90, 120, 180, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
1
3
0
1
Order By: Relevance
“…It0 et al [36] studied the PTH effect closely in chick osteoclast cultures and found that greater cyclic AMP responses to PTH occurred in cultures with greater degrees of contamination by alkaline phosphataserich cells. Our conclusion from that work [36] and our own data is that PTH does not increase cyclic AMP formation in either rat or chick osteoclasts; it is consistent with the view that the PTH response occurred in osteoblast-like cells and that the target cells in bone for the effect of PTH on cyclic AMP are exclusively cells of the osteoblast lineage [5,33].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It0 et al [36] studied the PTH effect closely in chick osteoclast cultures and found that greater cyclic AMP responses to PTH occurred in cultures with greater degrees of contamination by alkaline phosphataserich cells. Our conclusion from that work [36] and our own data is that PTH does not increase cyclic AMP formation in either rat or chick osteoclasts; it is consistent with the view that the PTH response occurred in osteoblast-like cells and that the target cells in bone for the effect of PTH on cyclic AMP are exclusively cells of the osteoblast lineage [5,33].…”
Section: Discussionsupporting
confidence: 84%
“…Finally, the results with PTH warrant comment. The fact that both PTH and calcitonin increase cyclic AMP production in bone has been explained by the PTH effect taking place in osteoblasts and the calcitonin effect in osteoclasts [33], but this has never been demonstrated directly until the present study. A biochemical response to PTH was noted in impure osteoclast cultures derived from both rat and chick, but PTH did not influence cyclic AMP formation in osteoclasts from either species as detected by immunocytochemistry.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…When using systemically administered therapy, however, there must be certainty that adequate concentrations of the therapeutic agent are attained in the infected tissue and joint space. Many studies of synovial fluid antibiotic levels after systemic administration have been conducted in horses (Beech et al ., 1977; Beech et al , 1979; Martin et al , 1980; Stover et al , 1981a,b; Brown et al , 1982; Soraci et al , 1996). Normal horses were used in all of these pharmacokinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Esto marca algunas diferencias con lo hallado para otros antibióticos betalactámicos en sinovia de equinos, como en el caso de cefapirina, en la que se reportó 4.6 pg/ml de concentración máxima (Brown et al, 1986), o tal como se reportó para cloxacilina, para la cual se hallaron concentraciones máximas de 4 gg/ml (Martin et al, 1980).…”
Section: Siembraunclassified